LANGUAGE STYLES USED BY MALE AND FEMALE BLOGGERS IN THE BLOGOSPHERE - RESMIHERTANTY, FARIDA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Interaction will not occur properly if someone does not speak with the right style.  In this study, the ways of bloggers comment the blog perhaps can be investigated from the characteristics of language styles to show casualty, intimacy, consultatively, deliberatively and oratorical. In addition, the characteristic of their language style perhaps show some phenomenon according to their sexual identity. This research is intended to answer: What language styles are used by male and female bloggers to express their thoughts on ontd_political.livejournal.com? The objective of the study is to get the deep description about the problem of the study which is defining male and female bloggers in using their language style on ontd_political.livejournal.com. Moreover, the study will find the dominant style that occur in the blog . The writer finds that male and female bloggers in the blogosphere use three kinds of language styles, which are; consultative, casual and intimate.  According to the result, casual style that dominates among others is more influenced by informal situation in the blog. The researcher concludes that setting and sexes are such factors that influence the language style that been used by bloggers to express their opinion in ontd_political.livejournal.com. In addition to their writing form, the researcher assumes that many bloggers use the typical of spoken language to write their comment.  They write by using the typical of spoken form language which has no formality and preplanning. Moreover, some of them use inappropriate words to be shown in written form. Therefore, the researcher concludes that the comments in the ontd_political.livejournal.com are not definitely as written form according to the language variety perspective. Key Words: Language Style, Male and Female and Blogosphere